Determination of Student Academic Fraudulent Behavior in the Misuse of Information Technology and Integrity - Dea Aulia; Yoni Hermawan; Sri Hardianti Sartika (Universitas Sebelas Maret, 2023)
This research focuses on academic cheating committed by students, intending to know the influence of misuse of information technology and integrity on students' academic cheating behavior. It is necessary to be known because academic cheating can influence the quality of human resources or graduates produced by an institution. The researchers in this study used the survey method with an explanatory design. This study involved Siliwangi University students with proportional random sampling techniques; as many as 354 students were involved as research samples and questionnaires for data collection techniques. The analysis method employed multiple linear regression, and the study's results stated that the misuse of information technology positively influenced 33.3% of academic cheating behavior, with sig. score of 0.000, and student integrity negatively influenced 4.6% of academic cheating behavior, with sig. score of 0.000. Besides, jointly, misuse of information technology and student integrity significantly influenced, with a sig. value of 0.000 and a percentage of influence of 37.9% on academic cheating behavior.